Prophylactic effect of UFT on the recurrence of bladder cancer - Naito, K (Hinyokika kiyo. Acta urologica Japonica, 1990)
To evaluate the effect of UFT, a mixture of ftorafur and uracil in a ratio of 1:4, in preventing postoperative recurrence of bladder cancer, we performed a randomized controlled study with a non-medication group as control. UFT was given orally 400 mg a day for 6 months. Of 111 patients, 56 were given UFT and 55 were followed up without any medication. The non-recurrence rate in the group treated with UFT was 62.8% after 1 year and 36.3% after 2 years of follow up, and that of the control group was 45.7% and 39.5%, respectively. The rate of non-recurrence in the UFT group was significantly higher (p less than 0.05) than that of the control group during the period of follow up for 2 years. The incidence of side effects was 6.8% in UFT patients. These results indicate the clinical usefulness of prophylactic administration of UFT for bladder cancer patients